2022
DOI: 10.5534/wjmh.210056
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Fragmentation: A Critical Assessment of Clinical Practice Guidelines

Abstract: Sperm DNA fragmentation (SDF) is implicated in male infertility and adverse reproductive outcomes. With the publication of many studies regarding the etiologies and contributors to SDF, as well as the effects of SDF, guidelines are necessary to aid clinicians in the application of SDF for male fertility evaluation. Two recent clinical practice guidelines were published by Agarwal et al and Esteves et al. In this article, we have evaluated and compared both guidelines. We have found fairly similar recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 25 publications
1
39
0
3
Order By: Relevance
“…Nevertheless, interest in using antioxidants to reduce potential SDF in these patients with almost total necrozoospermia is open for discussion. Antioxidants may indeed have a beneficial effect on reducing SDF [ 18 68 69 ].…”
Section: Management Of Necrozoospermiamentioning
confidence: 99%
“…Nevertheless, interest in using antioxidants to reduce potential SDF in these patients with almost total necrozoospermia is open for discussion. Antioxidants may indeed have a beneficial effect on reducing SDF [ 18 68 69 ].…”
Section: Management Of Necrozoospermiamentioning
confidence: 99%
“…In terms of reproductive outcome prediction, Esteves et al , concluded that SDF values of 20–30% appear to correlate with adverse pregnancy outcomes through either natural conception or assisted reproduction ( 97 ). Nevertheless, formal guidelines are warranted to alleviate the existing discrepancies and that can be clinically implemented to utilize the crucial information offered through this diagnostic utility ( 98 ).…”
Section: How To Select a Test For Sperm Dna Fragmentation?mentioning
confidence: 99%
“…Several strategies can be employed to reduce SDF among infertile men before natural or assisted reproduction to improve reproductive outcomes. Known underlying causes and risk factors of high SDF such as smoking and environmental exposures should be addressed ( 98 ). Also, suitable antibiotic therapy should be considered for male genital tract infections which are associated with elevated SDF ( 99 ).…”
Section: Management Of Elevated Sdfmentioning
confidence: 99%
“…In their guidelines, Agarwal et al (2020) [ 35 ], and Esteves et al (2021) [ 118 ] shared common ground in acknowledging the validity and reliability of SDF testing in varicocele patients, using any of the available assays, such as terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), Comet, sperm chromatin structure assay (SCSA), and sperm chromatin dispersion (SCD). Both guidelines also offered a cut-off of 20% to differentiate between fertile and infertile males and recommended SDF testing in case of unexplained or idiopathic male infertility, recurrent pregnancy loss, clinical varicocele, lifestyle risk factors (such as smoking, alcohol, obesity, and environmental exposures), and in the failure of assisted reproductive technology (ART) [ 35 118 119 ].…”
Section: Clinical Determination Of Oxidative Stress In Semen Analysismentioning
confidence: 99%
“…Agarwal et al (2021) [ 119 ], have recently stated that oral antioxidants, lifestyle modifications, recurrent ejaculation and controlling infections and inflammation can lower SDF. Additionally, men with high SDF and concurrent varicocele should consider undergoing varicocelectomy, while men with persistently high SDF are advised to perform intracytoplasmic sperm injection (ICSI) with sperm processing and preparation or to use testicular sperm in ICSI in the context of recurrent pregnancy loss with high SDF [ 119 ].…”
Section: Clinical Determination Of Oxidative Stress In Semen Analysismentioning
confidence: 99%